2010
DOI: 10.1089/ten.tea.2009.0131
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Differentiation Influences Stem Cell Migration Out of Scaffold-Free Microspheres

Abstract: Complete bone regeneration of critical-size defects frequently fail because of the use of acellular bone substitutes and because of partially negative influences of artificial scaffolds. However, the supply of cells to critical-size defects is essential for the regeneration. Therefore, engineered scaffold-free tissues, with outgrowing cells that fill up spaces in the bony defect, are promising candidates for bone regeneration approaches. Here, we demonstrate such a scaffold-free tissue construct (microspheres)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
(36 reference statements)
3
26
0
Order By: Relevance
“…Furthermore, their use does not raise ethical concerns [2,33,34] . The differentiation potential of USSCs into the osteogenic lineage is well known and has been verified by many research groups [36,40,41] . They can be differentiated into the osteogenic lineage both spontaneously and when cultured with specific supplements [36] .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, their use does not raise ethical concerns [2,33,34] . The differentiation potential of USSCs into the osteogenic lineage is well known and has been verified by many research groups [36,40,41] . They can be differentiated into the osteogenic lineage both spontaneously and when cultured with specific supplements [36] .…”
Section: Discussionmentioning
confidence: 79%
“…The differentiation potential of USSCs into the osteogenic lineage is well known and has been verified by many research groups [36,40,41] . They can be differentiated into the osteogenic lineage both spontaneously and when cultured with specific supplements [36] . The control of osteogenic differentiation of USSCs is important for in vitro culture or delivery by matrices.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…144 Moreover, the time for osteogenic priming was inversely related to the cell outgrowth from the aggregate. 145,146 In vivo studies in rabbits showed that aggregates of MSCs could adhere promptly on the osteochondral defects by surface tension and stay without any loss, improving cartilage regeneration. 22 Aggregate composites of chondrocytes and synovium-derived MSCs were injected to the osteochondral defects in a rabbit model, and effective restoration of articular cartilage and in vivo ECM production were observed.…”
Section: Msc Aggregates In Bone and Cartilage Regenerationmentioning
confidence: 99%
“…Use of skeletal or dental stem cells can be used in future to repair craniofacial region and may provide a promising alternative approach for reconstruction of craniofacial defects. Lagenbach et al2010 (43) in their in vitro studies used microspheres (scaffold free tissue construct) to close the bone defects. They found osteogenically differentiated microspheres with outgrowing cells can be used to fill up bone defects.…”
Section: Periodontal Regeneration:-mentioning
confidence: 99%